The production function of top R&D investors: Accounting for size and sector heterogeneity with quantile estimations - Antonio Vezzani; Sandro Montresor (European Commission, Joint Research Centre (JRC), 2013)
The paper investigates how top R&D investors differ in the production impact of their inputs and in their rate of technical change. We use the EU Industrial R&D Investment Scoreboard and perform a quantile estimation of an augmented Cobb-Douglass production function for a panel of more than 1,000 companies, covering the period 2002-2010. The results for the pooled sample are contrasted with those obtained from the estimates for different groups of economic sectors. Returns to scale are bounded by the initial size of the firm, but to an extent that decreases with the technological intensity of the sector. The output return of knowledge capital is the most important, irrespective of firm size, but in high-tech sectors only. Elsewhere, physical capital is the pivotal factor, although with size variations. The investigated firms appear different also in their technical progress: embodied in mid-high and low/mid-low tech sectors, and disembodied in high-tech sectors.
Keywords: D24; D21; O30; 330; production function; R&D; firm and sector heterogeneity